2013
DOI: 10.1007/s11764-013-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the status of A National Action Plan for Cancer Survivorship in the USA

Abstract: Purpose-There are currently more than 12 million cancer survivors in the USA. Survivors face many issues related to cancer and treatment that are outside the purview of the clinical care system. Therefore, understanding and providing for the evolving needs of cancer survivors offers challenges and opportunities for the public health system. In 2004, the Centers for Disease Control and Prevention and the Lance Armstrong Foundation, now the Livestrong Foundation, partnered with national cancer survivorship organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Some additional areas, however, such as developing clinical guidelines and assuring a quality workforce, require additional attention and reflect strategies more appropriate for organizations that provide clinical service delivery. 18 The assessment also found that an increased emphasis on evaluation and translation of research to practice were warranted—a particular strength of public health organizations. 18 There is a unique opportunity to integrate the SEM and NAPCS to provide an integrated model for public health action for cancer survivorship that is strategic, comprehensive, actionable, and measurable.…”
Section: Domains For Public Health Action: the National Action Plan Fmentioning
confidence: 99%
“…Some additional areas, however, such as developing clinical guidelines and assuring a quality workforce, require additional attention and reflect strategies more appropriate for organizations that provide clinical service delivery. 18 The assessment also found that an increased emphasis on evaluation and translation of research to practice were warranted—a particular strength of public health organizations. 18 There is a unique opportunity to integrate the SEM and NAPCS to provide an integrated model for public health action for cancer survivorship that is strategic, comprehensive, actionable, and measurable.…”
Section: Domains For Public Health Action: the National Action Plan Fmentioning
confidence: 99%
“…In a time when the long-term health and well-being of cancer survivors has been deemed a public health issue, 27 and stakeholders are being called on to intervene using approaches with broader reach, 28 this study offers valuable insights into further increasing awareness of dietary guidelines among CRC survivors. Perhaps the guideline in greatest need of increased awareness is that on limiting or avoiding alcohol; a sizable minority had never heard of this recommendation and many were unaware of alcohol’s potential harms to health.…”
Section: Discussionmentioning
confidence: 99%
“…For many diagnosed with cancer, survivorship means living with cancer as a chronic condition, while for others, although there may be no evidence of the cancer, there are bothersome longterm and persistent effects. The goal in cancer survivorship care is to provide the tools for survivors to live as healthy a life as possible, one devoid of additional chronic illness, and one in which late effects are minimized (Smith et al, 2013).…”
Section: Survivorship Guidelinesmentioning
confidence: 99%